Radiosonde Transmitter Meisei iMS-100 Study as Observation on Air at Meteorology Station Klas I Depati Amir Pangkalpinang - Arkan, Fardhan; Nababan, Demson (Journal of Electrical Technology UMY, 2017)
A radiosonde is one of the high technology tools and useful for aeronautical. In radiosonde have several sensors like air temperature, air pressure, air damp, vapor point, direction, and airspeed. Data from measure result will be received by supervising station in earth surface. Information will be collected by subarea air upstairs in Meteorology Station Klas I Depati Amir Pangkalpinang. An observation was done at 00.00 UTC (07.00 am) and at 12.00 UTC (07.00 pm). A transmitter in this observation is GPS Radiosonde iMS-100. The result shows that the radiosonde can work well at air pressure of 20 to 1000 hPa.